PELATIHAN PENGEMASAN MINYAK KELAPA PADA KELOMPOK WANITA TANI AL-UMMAHAT DI DESA LENDANG NANGKA - Rina Heldiyanti; Idiatul Fitri Danasari; Siska Ita Selvia; Ni Made Wirastika Sari (Universitas Mataram, 2023)
The Al-Ummahat Women Farmers Group is a group of productive women who produce various kinds of processed food products, but are still constrained by problems with product packaging. One of the superior products that need attention is coconut oil. The coconut oil produced by KWT has great potential to enter the modern market, but from a packaging point of view, it is still not feasible because it uses used plastic bottles and glass bottles. This service activity aims to provide traditional coconut oil packaging training to members of the KWT Al-Ummahat group, so as to create coconut oil that has selling value and attractiveness. The service method used is starting with a location survey to review the conditions and problems being faced by KWT. After getting the problem of community service activities, it is continued by providing socialization through presentations, demonstrations, packaging practices and evaluations. The output of this service activity is in the form of traditional coconut oil which has been packaged using polyethylene terephthalate (PET) bottles. Coconut oil that has been put into packaged bottles is then labeled with complete information such as brand, composition, manufacturer's address and contact, as well as the product's shelf life. Products that have been packaged and labeled are then ready to be marketed both offline in the modern market and online with a wider target market. Through packaging training, members are able to make products more attractive with proper packaging and product information, so they are ready to be marketed.